Localizing demand and supply of environmental services: interactions with property rights, collective action and the welfare of the poor - Swallow, Brent M.; Meinzen-Dick, Ruth S.; van Noordwijk, Meine (International Food Policy Research Institute, 2005)
Payments for environmental services (PES) are increasingly discussed as appropriate mechanisms for matching the demand for environmental services with the incentives of land users whose actions modify the supply of those environmental services. While there has been considerable discussion of the institutional mechanisms for PES, relatively little attention has been given to the inter-relationships between PES institutions and other rural institutions. This paper presents and builds upon the proposition that both the function and welfare effects of PES institutions depend crucially on the co-institutions of collective action (CA) and property rights (PR)... This paper presents a conceptual framework that clarifies the inter-linkages between property rights, collective action, payment for environmental services, and the welfare of smallholder land users. The framework is centered on concerns of function and welfare effects of PES. The functional perspective clarifies the effects of collective action and property rights institutions on the supply of environmental services. The welfare perspective considers smallholders as one of several potential sources of supply,sometimes directly competing against large landowners and public sector providers.